1993
DOI: 10.1080/00365519309088413
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and triglyceride synthesizing activities of fibroblast-like cells derived from epididymal and subcutaneous adipose tissues of rats

Abstract: Fibroblast-like cells from subcutaneous adipose tissue and epididymal adipose tissue were prepared from rats and their proliferation and [14C]deoxy-glucose uptake and triglyceride synthesis from [14C]palmitate were investigated. The proliferation of fibroblast-like cells from subcutaneous adipose tissue was greater than that from epididymal adipose tissue. Insulin enhanced the proliferation of fibroblast-like cells derived from subcutaneous adipose tissue, but not from epididymal adipose tissue. The uptake of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The relationship between subcutaneous and visceral adipocyte metabolism and development has been extensively studied using primary cell cultures isolated from fat tissue [20]. We have shown that adipocytes which accumulated in mesenteric area, and not in the subcutaneous area, induce TNF-a gene expression, thus leading to an increased concentration of TNF-a in the serum using a cell transplantation method in mice [14].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between subcutaneous and visceral adipocyte metabolism and development has been extensively studied using primary cell cultures isolated from fat tissue [20]. We have shown that adipocytes which accumulated in mesenteric area, and not in the subcutaneous area, induce TNF-a gene expression, thus leading to an increased concentration of TNF-a in the serum using a cell transplantation method in mice [14].…”
Section: Discussionmentioning
confidence: 99%